O nacionalismo em Theodoro Braga: posturas e inquietações na construção de uma arte brasileira - Coelho, Edilson da Silveira (2009)
Study the artistic path taken by the Brazilian artist, born in the State of Pará, Theodoro José da Silva Braga, or Theodoro Braga (1872-1953), bachelor of Laws, who chose the artistic and teaching career. Graduated by Brazilian National School of Fine Arts (Escola Nacional de Belas Artes – ENBA) in 1899, he has rewarded with a five-years improvement course in Europe. In Paris, he used to attend Jean-Paul Laurens’ atelier, where he got interested by historical painting. After two years in Paris, Braga traveled throughout many countries, always attracted by its cultural characteristics and artistic production. Back to his hometown in Brazil while the last years of Belle Époque (period of French influence in Brazilian colonization, particularly in fine arts and architecture), after a decorative art exposition where he presented his ornamental project based in Brazilian fauna and flora, he met the intendant Antônio Lemos, who became his greatest patron. Lemos invited him to paint A fundação da cidade de Belém ("The foundation of city of Belém", capital fo Pará), an artistic and historical invaluable piece. When he noticed the ceramic art done by the ancient Indians from Marajó Island, in the north of State of Pará, he decided to engage in an exhaustive research that would help him to support his proposal of nationalization of Brazilian Art. In Belém, his initial teaching experiences were in Liceu Paranaense and Lauro Sodré Institute. Transferred to Rio de Janeiro to join the Brazilian Centenary of Independence, Braga worked hard to disseminate his nationalist thoughts. At this time, he taught in the ENBA and other professional institutes. Some years later, he move to São Paulo, where he took part in the foundation of the Academy of Arts of São Paulo (Academia de Belas Artes de São Paulo), Mackenzie Institute and Brazilian School of Art (Escola Brasileira de Arte). There, he lived and worked until the end of his life. His artistic production includes an ornamental project of decorative art, many historical paintings, various illustrations and Art teaching. He used his Lawyer skills to discourse and write articles and books about Art Education, in which he emphasized how important was the professional development to the conception of an authentic Brazilian Art. According to his proposal, the Brazilian nature and the ancient Marajó natives Arts, not foreign models, should be the source of Brazilian art inspiration. Persistent in his ideologies, he built and decorated his residence in São Paulo, called Retiro Marajoara (or "Marajoara Retreat", a kind of town-house inspired in the Art from Marajó ancient Indians), and believed that Art Education would be the potential pathway for the construction of a genuine Brazilian Art.